Pengaruh Peer to Peer (P2P) Lending Terhadap Pembiayaan Bank Syariah Di Indonesia: Peluang Atau Ancaman Bagi Bank Syariah? - Ahmad Fatoni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to examine the effect of Peer to Peer (P2P) lending on Islamic bank financing in Indonesia. This study uses panel data using a sample of Islamic Commercial Banks in 33 provinces in Indonesia. The type of data used is secondary data, namely quarterly data from the period December 2019 to March 2021. This study uses the Fixed Effect Model as the best estimation model. The results showed that the distribution of P2P lending has a positive and significant effect on Islamic bank financing. The results of this study prove that P2P lending is not a threat, but as a complementary to Islamic banks which is realized by collaboration between P2P lending and Islamic banks.